Transcatheter Closure of Patent Ductus Arteriosus in Premature Infants With Very Low Birth Weight - Wang, Jieh-Neng; Lin, Yung-Chieh; Hsieh, Min-Ling; Wei, Yu-Jen; Ju, Ying-Tzu; Wu, Jing-Ming (Frontiers in Pediatrics, 2021)
Background: The aim of this study was to describe our experience with transcatheter device closure of PDA in symptomatic low-birth-weight premature infants. Methods: We performed a retrospective study of infants born with a birth body weight of less than 2000 g and admitted to National Cheng Kung University Hospital from September 2014 to December 2019. Basic demographic and clinical information as well as echocardiographic and angiographic data were recorded. Results: Twenty-five premature infants (11 boys and 14 girls) born at gestational ages ranging between 22 and 35 weeks (mean, 25 weeks) were identified. The mean age at procedure was 34.5 ± 5.5 days, and the mean weight was 1209 ± 94 g (range, 478-1980 g). The mean diameter of the PDA was 3.4 ± 0.2 mm (range, 2.0-5.4 mm). The following devices were used in this study: Amplatzer Ductal Occluder II additional size (n = 20), Amplatzer Vascular Plug I (n = 1), and Amplatzer Vascular Plug II (n = 4). Complete closure was achieved in all patients. The mean follow-up period was 30.1 ± 17.3 months (range, 6-68 months). In total, 3 patients had left pulmonary artery (LPA) stenosis and 1 patient had coarctation of the aorta during the follow-up period. Younger procedure age and smaller procedure body weight were significantly associated with these obstructions. Conclusions: Performing transcatheter PDA closure in symptomatic premature infants weighing more than 478 g is feasible using currently available devices; moreover, the procedure serves as an alternative to surgery.